Peran Strategi Manajemen Sumber Daya Manusia dalam Menciptakan Pendidik Berkualitas Unggul: Pendekatan Systematic Literature Review (SLR) - Muhamad Saleh Sukiman (WISSEN : Jurnal Ilmu Sosial dan Humaniora, 2025)
This study is driven by the pressing necessity for educational institutions to possess skilled and high quality workforce to ensure educational achievement. Human resource administration plays a strategic role in enhancing individual contributions toward achieving academic objectives. The quality of school HR is a crucial factor in determining both educational standards and outcomes. The purpose of this research is to explore how personnel administration contributes to the creation of superior HR within schools. A Systematic Literature Review (SLR) approach was employed, analyzing 30 articles accredited at the national level sourced from Google Scholar. The systematic literature review method was selected since it provides a thorough understanding and integrates findings from a range of pertinent studies, leading toward more credible and dependable conclusions. The findings indicate that HR administration is a key element in developing excellent educational staff through several mechanisms, including administrative oversight, educator hiring and screening, capacity building, and work performance assessment, well being and equitable remuneration and institutional culture building, and dispute resolution. These interrelated elements collectively contribute to forming superior HR, consequently enhances the general standard of education. This study provides a significant contribution to understanding the pivotal role of HR management within educational settings and presents effective approaches that schools can implement to strengthen the standard of their educational staff.